Dopant effects on conductivity in copper oxide photoelectrochemical cells. (15th February 2016) - Chiang, Chia-Ying; Shin, Yoon; Ehrman, Sheryl
Highlights: CuO doped with Li, Ni, Co, Ag, Zn and Mg, the conductivity of the films increases. The addition of Cr, Fe, and Mn introduced into CuO film leads to lower conductivity. A correlation between the photocurrent density and conductivity is reported. Increase of film conductivity can lead to a higher photocurrent density. Abstract: Hydrogen generation from water splitting reaction with the energy from sunlight via a photoelectrochemical (PEC) cell is one of the ultimate goals in the renewable energy field. In the PEC process, energetic excited electrons can go through fast recombination with the holes, resulting in photon energy waste and lowering the solar to hydrogen conversion efficiency. So it is essential to increase the conductivity and lower the resistance of the photoelectrodes. Here, copper oxide thin film was chosen for the demonstration of the importance for the conductivity of the film toward the photocurrent density generation. By doping with Li, Ni, Co, Ag, Zn and Mg, the conductivity of the films increases from 3 × 10 −6  S/cm for the intrinsic CuO film to up to 10 −4  S/cm, two orders of magnitude higher, and thus leading to up to four folds increase in photocurrent density. On the other hand, the addition of Cr, Fe, and Mn introduced into CuO film leads to lower conductivity, to 10 −8 –10 −9  S/cm, and leads to a significant decrease of the photocurrent density. A correlation between the photocurrent density and conductivity is also reported in this study.